Increasing the Growth and Quality of Oil Palm Seeds (Elaeis guineensis Jacq) by Selecting the Position of Fruit Bunches and Dormancy Breaking Methods - Mansur Siregar; Devi Andriani Luta; Najla Lubis (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Oil palm reproduces by seeds and will germinate to grow further into plants. This study aims to determine the effect of the position of fruit bunches and various methods of breaking dormancy on the germination of coconut seeds palm. This study used a completely randomized design (CRD) factorial consisting of 2 factors with 18 combinations and 2 replications. The first factor is the position of the fruit on the oil palm bunch which consists of 6 positions of the fruit bunch, as follows: the base of the inner fruit bunch (PT), the base of the outer fruit bunch (PL), the middle of the inner fruit bunch (TD), the middle of the inner fruit bunch outer (TL), inner fruit bunch tip (UD), outer fruit bunch tip (UL) The second factor is various methods of breaking dormancy with the symbol (P), namely Ecoenzyme Soaking (P1), Gibberellin Soaking (P2), oven system ( P3). Parameters observed included germination rate (%), percentage of normal sprouts (%), percentage of abnormal sprouts (%), radicle exit age (days), plumule exit age (days), radicle length (cm) and plumule length (cm). The results showed that the position of the oil palm fruit bunches and the dormancy breaking method gave a significant response to the germination parameters of 53.33% (fruit bunches) 49.33% (oven system), normal germination percentage 43.33% (fruit bunches) 38.89% (oven system), radicle exit age 36 days (bundle position) 37.17 days (oven system), plumule exit age 54.67 days (fruit bunches) 59.25 days (oven system), radicle length 1.98 cm (bunch position) 1.60 cm (oven system), and plumule length 1.78 cm (bunch position) 1.42 cm (oven system) and gave no significant response to the percentage of abnormal sprouts (%). The best treatment was the position of the deep base fruit bunches and oven system